2005
DOI: 10.1079/bjn20051517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ruminal administration ofEscherichia coliwild type or a genetically modified strain with enhanced high nitrite reductase activity on methane emission and nitrate toxicity in nitrate-infused sheep

Abstract: The effects of two kinds of Escherichia coli (E. coli) strain, wild-type E. coli W3110 and E. coli nir-Ptac, which has enhanced NO 2 reduction activity, on oral CH 4 emission and NO 3 toxicity in NO 3 -treated sheep were assessed in a respiratory hood system in a 4 £ 6 Youden square design. NO 3 (1·3 g NaNO 3 / kg 0·75 body weight) and/or E. coli strains were delivered into the rumen through a fistula as a single dose 30 min after the morning meal. Escherichia coli cells were inoculated for sheep to provide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
5
26
1
Order By: Relevance
“…These values were lower than those obtained by Marden et al (2005) in dry cows ranging from -173.5 to -216.8 mV when testing a new device for the continuous measurement of ruminal parameters in the absence of oxygen. Barry et al (1977) reported a range of Eh in sheep from -150 to -260 mV, while Mathieu et al (1996) or Sar et al (2005) presented lower values ranging from -319 to -290 mV. However, data presented in the latter studies are not fully comparable with results of Marden et al (2005) and ours because they ex- …”
Section: Discussioncontrasting
confidence: 56%
“…These values were lower than those obtained by Marden et al (2005) in dry cows ranging from -173.5 to -216.8 mV when testing a new device for the continuous measurement of ruminal parameters in the absence of oxygen. Barry et al (1977) reported a range of Eh in sheep from -150 to -260 mV, while Mathieu et al (1996) or Sar et al (2005) presented lower values ranging from -319 to -290 mV. However, data presented in the latter studies are not fully comparable with results of Marden et al (2005) and ours because they ex- …”
Section: Discussioncontrasting
confidence: 56%
“…Data indicated that nitrate-reducing bacteria could be used to prevent accumulation of nitrite when sodium nitrate is used to reduce methane emissions in vitro (Sakthivel 2010 ). Sar et al ( 2005 ) reported that nitrate inhibits methanogenesis signifi cantly in sheep at the rate of 1.3 g NaNO 3 /kg W 0.75 of the animals, but it was accompanied with higher levels of plasma nitrite and blood methaemoglobin. These negative effects of nitrate feeding could be reduced or completely removed by feeding Escherichia coli culture at the rate of 150 ml (2 × 10 10 cells/ml), which had a capability to reduce nitrite with nitrite reductase activity.…”
Section: Nitrate-/nitrite-reducing Bacteriamentioning
confidence: 96%
“…The nitrate was not having any effect on VFA concentration, but there was a shift in molar proportion of VFA with higher acetate, lower propionate and lower butyrate along with less methane production. Sar et al ( 2005 ) suggested that E. coli W3110 plus nitrate and E. coli nir-Ptac plus nitrate both have potential to be used as feed additive to mitigate methane production (6-12 %) in sheep. Van Zijderveld et al ( 2010 ) assessed the effect of dietary addition of nitrate (2.6 % of DM) and sulphate (2.6 % of DM) on methane emission in lambs.…”
Section: Inorganic Compoundsmentioning
confidence: 99%